Treatment of mental health illness by Afrikaans speaking church leaders in Polokwane Limpopo Province - Kruger, Qunessa (University of Limpopo (Turfloop Campus), 2012)
South Africa has a growing rate of mental health care users. Because of the lack of health resources and personal beliefs many of these mental health care users consult with their church leaders. The treatment of mental illness by clergy in South Africa is largely undocumented. The aim of the study was to explore and describe the treatment of mental illness by Afrikaans speaking church leaders in Polokwane, Limpopo Province. To gain a deeper understanding of the views held by the Afrikaans-speaking church leaders, a qualitative approach was utilized. Ten participants agreed to participate in the study. The results tend to suggest that most of the respondents use a combination of supportive therapy and teachings from scripture to treat some mental illnesses, and that they feel positive towards collaboration with other mental health care professionals. Lastly the results indicated that most respondents emphasized the importance of homophily in referral criteria. Key Concepts Mental illness; Christian church; Afrikaans speaking; church leader; treatment
Thesis (M.A. (Clinical Psychology)) --Univesity of Limpopo, 2013
Keywords: Mental illness; Christian church; Afrikaans church leaders; 362.198; Mental illness -- South Africa; Mental illness -- Treatment; Church work with people with mental disabilities